Crystal structure of 4-methyl-N-[2-(piperidin-1-yl)ethyl]benzamide monohydrate - B. K. Revathi; D. Reuben Jonathan; S. Sathya; K. Prathebha; G. Usha (Acta Crystallographica Section E: Crystallographic Communications, 2015)
In the title compound, C15H22N2O·H2O, the dihedral angle between the planes of the piperidine and benzene rings is 31.63 (1)°. The piperidine ring adopts a chair conformation. The water solvent molecule is involved in interspecies O—H...O, O—H...N, N—H...O and weak C—H...O hydrogen-bonding interactions, giving rise to chains extending along [010].